An investigation of high intensity ultrasonication and chemical immersion treatments on Campylobacter jejuni and spoilage bacteria in chicken. (February 2018) - Kassem, Ahmed; Meade, Joseph; McGill, Kevina; Walsh, Ciara; Gibbons, James; Lyng, James; Whyte, Paul
Abstract: High intensity ultrasonication (US) alone or in combination with chemical immersion treatments of lactic acid (3% LA), sodium decanoate (3% SD) and trisodium phosphate (10% TSP) were investigated to reduce populations of Campylobacter jejuni and spoilage organisms in raw chicken. Different experimental conditions were used including a range of temperatures (4 °C, 25 °C and 54 °C) and exposure times (1, 2 and 3 min). All combination treatments significantly reduced C. jejuni compared to their individual treatments while only the combination US + SD significantly reduced Total Viable Count (TVC). Multiple linear regression predicted bacterial reductions resulting from changing treatment, temperature and time or each group of microorganisms. Increasing temperature from 4 °C to 54 °C would enhance C. jejuni, TVC and Total Enterobacteriaceae Count (TEC) reductions by 0.73, 1.02 and 1.37 log10  cfu/g respectively. Increasing time from 1 to 3 min enhanced bacterial dependent of C. jejuni and TEC by 0.49 and 0.31 log10  cfu/g respectively. Industrial relevance. This study demonstrates the potential application of high intensity ultrasomication alone or in combination with chemical treatments to reduce bacterial contamination of chicken carcasses. Different tempretures and times were investigated to optimize the most effective treatments conditions in chicken abattoirs. Highlights: US-chemical combinations significantly reduced C. jejuni counts. Only US-SD significantly reduced TVC count. Temperature and time significantly affected levels of C. jejuni and TEC. Temperature had a significant affect on TVC.